Total knee arthroplasties performed with a mini-incision or a standard incision. Similar results at six months follow-up - Hernandez-Vaquero, Daniel (BioMed Central, 2010)
BACKGROUND: Minimal invasion surgery (MIS) is a recent technique recommended for Total knee arthroplasty (TKA) but demands an effort of the surgeons and the learning curve may be long. METHODS: Twenty six MIS-TKA were matched to 36 standard TKA with respect to age, sex, body mass index or preoperative score. All patients suffered from knee osteoarthritis, which had not improved with medical treatment and which presented a less than 10° deformity in the coronal and sagittal radiographic projections. At six months after the surgery a specific questionnaire was completed as well as the KSS (Knee Society rating scale), the generic short-form health questionnaire (SF-12) and a visual analogue scale (VAS). RESULTS: The MIS technique required more time of surgery (p < 0.001), hospital stay was noticeably shorter (p < 0.05) and drainage volume collected after surgery was significantly higher in the standard technique. We observe a higher frequency in small sizes implants for MIS surgery but no statistically significant differences were found between both groups regarding the radiological alignment of the implant. At six months no differences were found between the groups in range of motion, KSS scores, the physical or mental subscale SF-12, patient's pain perception, satisfaction or subjective improvement. CONCLUSIONS: Minimal invasion surgery in total knee arthroplasty showed no improvement over a standard approach.